Empowering Afghan women: The role of the internet in advancing gender equality - Afif, Sara; Quraishi, Tamanna; Farhangi, Fakhriea; Naimi, Ay Gul; Hashimi, Farzana; Noori, Haniya; Amiry, Sadaf (Institute of Education and Social Research, 2024)
This study investigates the influence of internet access and online platforms on Afghan women's empowerment, focusing on educational, economic, and social dimensions. The purpose is to examine perceptions among 120 participants from Zan Online University regarding these influences. The research employs a quantitative approach with a survey method to gather data on perceptions of educational effectiveness, economic opportunities, remote work facilitation, advocacy support, and public discourse participation. Findings reveal a predominantly positive perception of internet tools in enhancing educational opportunities (65.83% effective or very effective), fostering economic empowerment (66.67% very helpful or extremely helpful), and facilitating remote work (54.17% significant or extremely significant contribution). However, opinions vary on the influence of online communities on advocacy efforts (62.50% moderate to very influential) and support networks in public discourse (61.67% agree or strongly agree). These results underscore the internet's potential in empowering Afghan women while highlighting areas needing improvement and further exploration. The conclusion synthesizes these findings, suggesting continued support for internet infrastructure and tailored educational initiatives to maximize benefits for Afghan women's empowerment.